Approaches to rational development of analytical methods for mineral raw materials and products of their processing - B. A. Ovezov (Известия высших учебных заведений: Геология и разведка, 2023)
Background. Russia occupies a leading position in the global extraction of minerals, meeting all the demands of Russian economy. The efficiency of resources development determines the efficiency of both the oil and gas industry, as well as related economic sectors. At any stage, geological prospecting and exploration works are carried out sequentially and assume identification of the quantity, quality, shape and size of the valuable component contained in the deposit. In Russia, the recent trend in the development of laboratory research methods consists in creating and implementing hardware approaches capable of identifying the content of valuable components rapidly and accurately.Aim. To compare the existing approaches for obtaining the proportionality coefficient depending on the specifics of the ore deposit under exploration and to analyze the dependence of the amount of laser sampling of microprobes on the relative standard error of sampling the main general sample.Materials and methods. The Richards–Chechott equation and Demond and Halferdahl works were studied. An analysis of error classes was carried out.Results. The relative standard error of sampling the main general sample was found to decrease with an increase in the number of microsamples (pulses). The number of microprobes of an analytical sample depends on the heterogeneity of the valuable component distribution.Conclusion. An increase in the number of laser sampling of microsamples (pulses) leads to a decrease in the relative standard error of sampling the main general sample. The number of microprobes of an analytical sample depends on the heterogeneity of the valuable component distribution (K, α).